THE EFFECT OF USING EXPLICIT INSTRUCTION STRATEGY ON STUDENTS’ LISTENING COMPREHENSION OF PROCEDURE TEXT (A Study at the Eleventh Grade Students of SMK Negeri 1 Angkola Timur) - MARIANI HASIBUAN (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The objectives of the is research are to find out:a) The extent of the application description of using explicit instruction strategy on students’ listening comprehension of procedure text b) The extent of the students’ listening comprehension of procedure text before and after using explicit instruction strategy, and c) Whether there is any significant effect of using explicit instruction strategy on students’ listening comprehension of procedure text. The population of this research is all the eleventh grade students of SMK Negeri 1 AngkolaTimur which are divided into five classes and total are 145 students. The sample is taken from the population by using systematic sampling by using multiple of five. Therefore, sampling of this research is 29 students. This study is carried on by using experimental method. The data is collected by giving observation and test. The writer uses statistic processes in analyzing data by using formula of ttest. After collecting the data, it is found that the application of using explicit instruction strategy on students’ listening comprehension of procedure text is 3.5. It is categorized “Very Good”. The students’ listening comprehension of procedure text before using explicit instruction strategy is 76.21, it is categorizes “Good”. Then, students’ listening comprehension of procedure text after using explicit instruction strategy 80, it is categorized “Very Good”. There is a significant effect of using explicit instruction strategy on students’ listening comprehension of procedure text at the eleventh grade students of SMK Negeri 1 AngkolaTimur (to 4.15 >ttable 2.05). Therefore, Ha is accepted. Keywords: Explicit Instruction Strategy, Listening, Comprehension, Procedure Text.